P-031 Endovascular treatment in young adults with acute ischemic stroke: a single center experience. (12th July 2011) - Mehta, S; Sharma, J; Masoud, H; Chowdhry, S; Nanda, A; Sila, C; Blackham, K
Abstract : Objective: To assess the safety and efficacy of different endovascular treatment modalities in young adults with acute ischemic stroke (AIS). Background: Stroke in young adults is less common compared to the elderly but forms a significant burden in terms of morbidity and mortality. Endovascular therapies for AIS are relatively new modalities showing great promise. Data regarding their efficacy in this population is scant. Design/Methods: Retrospective chart review was performed in 188 consecutive patients who underwent endovascular treatments for acute ischemic stroke at our center between 2005 and 2009, and the patients between the ages of 18–45 were selected for further review (n=11). Their demographics were studied and the outcomes measured were post intervention rates of recanalization, asymptomatic and symptomatic hemorrhages and mortality. Results: Of the 11 patients age 18–45 (mean age 38.63±8.26), 54%(n=6) were female, 27.2% (n=3) were hypertensive and 9% (n=1) patients were diabetic. The mean NIHSS on admission was 15 and that on discharge was 6.5. The majority of the patients (n=9) had lesions in the anterior circulation, 5 of which were in the internal carotids, 2 were proximal MCA and 3 were distal MCA (M2/M3) branches. Vertebral and basilar artery occlusions were found in one patient each. All of these patients received a combination of intravenous and intra-arterial tPA. In addition, three patients received mechanical thrombectomy with MERCI (n=2) or Penumbra (n=1) retrieval devices. Complete recanalization (TIMI 3) was achieved in 27.2% (n=3) patients; partial recanalization (TIMI 2) was achieved in 54.5% (n=6) patients and no recanalization in 18.1% (n=2) patients. 18.1% (n=2) patients had asymptomatic and none(n=0) of the patients had symptomatic intracerebral hemorrhages detected on follow-up CT scans at 24 h post procedure.There were no mortalities. Conclusions: Combined intravenous and endovascular therapies proved to be a relatively safe and efficacious treatment modality for young patients with acute ischemic stroke, and these patients tended to have better outcomes than those reported for the general population.